Microbiology Factor Measurement as Indoor Air Quality Parameter in Public Space - Oktofa Setia Pamungkas; Henny Ayu Nirwala; Dina Mala Pardede (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
Nearly 90% of people spend their time in both private and public indoor spaces. Bank is one of the public indoor spaces accessible to the community, as well as a place for some workers spending time every day. This study was conducted in 6 banking sectors in Samarinda, East Kalimantan, focusing on the existence of microorganisms such as bacteria and fungi/mold. The purpose was to investigate the number of microorganisms, both bacteria and fungi, contained in indoor areas of several bank offices in Samarinda. The results showed that the number of bacteria and fungi at several sampling points in 6 offices were above the standard of Permenaker RI No. 5 the year of 2018 and Permenkes RI No. 48 the year of 2016, i.e.,>700 cfu/m3 for bacteria and >1000 cfu/m3 for fungi.